IDENTIFIKASI JENIS LALAT BUAH (Bactrocera spp) DI GALELA KABUPATEN HALMAHERA UTARA DENGAN MENGGUNAKAN PERANGKAP METIL EUGENOL - Sunarno Sunarno (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Studies on the Identification Type Fruit Fly (Bactrocera spp) in the Galela, North Halmahera by Using Methyl eugenol traps " made in the Galela, North Halmahera in the month of July-August 2014. This study aims to. Knowing the type of fruit flies (Diptera : tephritid) of the genus Bactrocera spp which attack plants Horticulture in the Galela , Knowing the type of the genus Bactrocera fruit flies , the dominant spp Hottikultura attack plants in the region Galela . The research was conducted by means of methyl eugenol trap pocket as high as 1-1.5 m , a total of 18 traps for 1 month . Results of research on fruit flies get caught in a trap in the area Galela , North Halmahera regency as many as 6714 birds. In the area there are 7 types Galela pest fruit flies is the most dominant B. carambolae (33 %) , and is extensible at least B. curvifera (Walker)(0.1 %)